HPLC electrochemical detection of trace amines in human plasma and platelets and expression of mRNA transcripts of trace amine receptors in circulating leukocytes - D'Andrea, Giovanni; Terrazzino, Salvatore; Fortin, Dino; Farruggio, Angelo; Rinaldi, Luciano; Leon, Alberta (Neuroscience letters, 2003)
We evaluated, using a multi-channel electrochemical HPLC system, whether trace amines are detectable in plasma and platelets of healthy control subjects. To this end, levels of tyramine, octopamine and synephrine were assessed in samples obtained from eight males and eight females, age matched and free from drugs. In plasma, octopamine was detectable in all subjects, synephrine in 15 and tyramine in six out of 16 subjects. Likewise, detectable levels of octopamine together with synephrine were, in contrast to tyramine, found within platelets of most individuals. Intracellular levels of the amines significantly diminished following platelet activation (ADP or collagen). In addition, circulating leukocytes from these same subjects are herein shown to express mRNA transcripts for the recently discovered ‘trace amine receptors’ (TAR-1, -3, -4 and -5). Thus, although baseline plasma levels of octopamine tyramine or synephrine may vary among healthy individuals, the observation that platelets store and actively release these trace amines suggests that they may be effectors involved in platelet-mediated signaling events in the bloodstream.